Laplacian lines for real-time shape illustration - Zhao, Yuan (2015)
Polygonal mesh is the collection of vertices, edges and surfaces that defines the shape of a 3D object. Feature lines are salient surface characteristics that are the curves on the surfaces of 3D object. Their definition involves third and fourth order surface derivatives. Therefore, line drawing is an effective way and commonly used for sketches, animations, and technical illustrations. In this project, the feature lines are found by object-space line drawing algorithm that can generate Laplacian lines based on the view point in real time. Two kinds of feature lines are defined based on this algorithm: silhouette of 3D object is defined as the zero-crossing points of the surface illumination and Laplacian lines are defined as the set of zero-crossing points to be computed by the Laplacian of the surface illumination. Compared with other third-order derivatives feature line detection algorithms, most of complex computations can be processed before the main process of the algorithm. In this project, a desktop application is implemented to draw two kind feature lines: silhouette and Laplacian lines of a given model through the stated algorithm. The analytic project report is based on the results of different models obtained by this algorithm.